Plan de mejoramiento para la gestión de la seguridad vial en la Concesión Bogotá –Villavicencio para el PR 6+800 al PR 8+000 (2022)
This document is aimed at improving road safety in the section from PR 6+800 to PR 8+000 supported by the ISO 39001 Standard. It is the standard directly related to the conservation of human lives and leads us to adopt a Management System of Road Safety essential for those organizations that carry out a large part of their work in means of transport. The ISO 39001 standard includes the standards that a company must meet in order to adopt a Road Safety Management System (SV), also called Road Traffic Security (RTS). This is a very necessary standard for those organizations or companies that carry out their work or part of it on the road.